Self-translation: a faithful rendition or a rewriting process? Haikal’s Autumn of Fury as an example - Al-Harahsheh, Ahmad Mohammad; Al-Omari, Mariam (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to investigate if self-translation is a true interpretation of a Source Text (ST) into a Target Text (TT), or if it is in fact a rewriting process. The study examines Haikal’s self-translation of a book titled ‘Autumn of Fury: The Assassination of Sadat’. This self-translation is used as an example due to the modifications and changes made by Haikal, and examines to what extent the translator is faithful to his ST (English version). For the purpose of this study, fifteen examples have been selected from Haikal's version of Autumn of Fury. They are then analysed and compared to their Arabic translations (TT), and the differences are highlighted and discussed. The selected examples include words, phrases, sentences, and sometimes whole paragraphs. The study relies on Critical Discourse Analysis (CDA) as a theoretical framework to uncover the hidden ideologies and attitudes behind the modification, manipulation, or rewriting of the ST into Arabic. These examples are analysed from linguistic, political and ideological perspectives. The study finds that Haikal’s self-translation of Autumn of Fury into Arabic was actually a rewriting process rather than a translation process, and that a new book is almost recreated out of the original.